France-Algérie : l’impact de l’histoire commune - Tahar Khalfoune (L’Année du Maghreb)
This reflection deals with the impact of a shared history – a century and thirty-two years of colonization and the tumultuous relationships after the independence – with the construction of Algeria, but also of today’s France. More than half a century after the independence, there is no doubt about the centrality of the Franco-Algerian question. On either side of the Mediterranean, this colonial past still continues to feed memories, resentments, mistrust, conflicts ... but also the ties, the cordial relationships, the cooperation ... whereas everything would lead observers to believe that the traumas of colonization and of the war of Algeria would oppose these two countries definitively. The weight of the colonial past and the complex and peculiar relationships that they maintain more than half a century after the severing of the links, oscillating since 1962 between tensions and detente, continue to polarize the passions, and weigh heavily on the construction of Algeria. But to a lesser extent, we must not be mistaken about the influence they have also exerted on the evolution of France.